Performance of Malaysian kenaf Hibiscus cannabinus callus biomass and exopolysaccharide production in a novel liquid culture - Norhisham, Danial ‘Aizat; Md Saad, Norsharina; Ahmad Usuldin, Siti Rokhiyah; Vayabari, Diwiya A G; Ilham, Zul; Ibrahim, Mohamad Faizal; Pau-Loke, Show; Wan-Mohtar, Wan Abd Al Qadr Imad (Taylor & Francis, 2023)
The versatility of a well-known fibrous crop, Hibiscus cannabinus (kenaf) is still relatively new to many. Kenaf’s potential applications, which can be extended even into critical industries such as pharmaceutical and food industries, have always been overshadowed by its traditionally grown fiber. Therefore, this study aimed to venture into the biotechnological approach in reaping the benefits of kenaf through plant cell suspension culture to maximize the production of kenaf callus biomass (KCB) and exopolysaccharide (EPS), which is deemed to be more sustainable. A growth curve was established which indicates that cultivating kenaf callus in suspension culture for 22 days gives the highest KCB (9.09 ± 1.2 g/L) and EPS (1.1 ± 0.02 g/L). Using response surface methodology (RSM), it was found that sucrose concentration, agitation speed, and naphthalene acetic acid (NAA) concentration can affect the production of KCB and EPS significantly (p < 0.05) while 2,4-dichlorophenoxy acetic acid (2,4-D) was deemed insignificant. To maximize the final yield of KCB and EPS, the final optimized variables are 50 g/L sucrose, 147.02 rpm, and 2 mg/L of NAA. To conclude, the optimized parameters for the cell suspension culture of kenaf callus serve as the blueprint for any sustainable large-scale production in the future and provide an alternative cultivating method to kenaf traditional farming.